User Manual: Google earth engine script for semi-automated mapping of small reservoirs using sentinel-2 satellite imagery - Amponsah, Mary; Zwart, Sander J.; Akpoti, Komlavi (International Water Management Institute, 2022)
This user manual describes the methodology to be followed to use the Google Earth engine script for semi-automated mapping of small reservoirs using Sentinel-2 satellite imagery. It is developed to support suitability analysis for multiple uses (including fisheries) of reservoirs in Ghana.